(untitled) (Journal of International Studies, 2020)
Today the emergence of a new "Asian order" is being touted, especially with the rise of China and India as two key and influential players. Where does Japan stand in this new Asian order and what role it might play in it? Given Japan’s location on the far eastern edge of the Asian continent its relations with the rest of Asia have always been challenging. Now Japan stands at a major crossroads in its relations with these now also successfully modernised Asian nations. Its status is transforming from the Asian leader to an Asian leader amidst rapid change in the politico-economic and security environment externally and domestic politico-economic and social change. These complex circumstances present new and very different challenges to Japan-Asia relations, especially since Japan’s place in Asia profoundly influences Japan’s place in the world. Early in the twenty-first century, Japan’s central foreign policy challenge is how to balance support for the US as its key ally across the Pacific, while maintaining, and possibly expanding, its influence in Asia. The main argument of this paper is that Japan’s contributions will remain vital - to Asia, to the Asia-Pacific and indeed to the overall global community. The September 2009 political change from the Liberal Democratic Party to the Democratic Party of Japan brings even stronger message from Japan of its Asian commitment.